Factors That Influence Impulsive Buying - Lia Ria Tuljanah; Rhian Indradewa (Dinasti International Journal of Education Management And Social Science, 2024)
This research uses a quantitative approach with an associative type, namely the research tries to explain the relationship between variables. The type of data used is primary data, which is data that is sourced or managed directly by researchers. Data collection in this research was carried out through a questionnaire using Google-form. The sample in this study was individuals who had shopped online at Shopee with a minimum age of 17 years. Determination of the sample size is based on that sampling must be at least 5-10 times the number of questionnaires. This research uses a Structural Equation Model (SEM) approach with a measurement model using the Smart PLS version 3.2.9 program. Furthermore, the research results show that functionality components and experimental marketing have a significant positive effect on attitudinal loyalty, while psychological components have no effect on attitudinal loyalty. Furthermore, attitudinal loyalty is proven to have a significant positive effect on impulsive buying. However, self-control cannot moderate the influence of attitudinal loyalty on impulsive buying.